PECULIARITIES OF THE STATE'S ACTIVITY IN THE FOREIGN EXCHANGE MARKET OF UKRAINE - REKUNENKO, Ihor; CHUKHNO, Ruslana (Scientific journal «World of Finance», 2021)
Introduction. One of the urgent and urgent problems today is the effective activity of the state in the foreign exchange market of Ukraine, which in an unstable economic situation should be primarily aimed at stabilizing and supporting the national currency, which in turn will create a basis for economic growth and support economic processes in the country, establishing international relations and increasing the competitiveness of the economy as a whole.The purpose of the article is to study the peculiarities of the state's activity in the foreign exchange market of Ukraine, to determine the factors and problems that affect its condition.Results. This paper considers the peculiarities of the state's activity in the foreign exchange market, the regulator of which is the National Bank of Ukraine, which carries out operations in the foreign exchange market in order to stabilize the official exchange rate of the national currency. It was found that the introduction of the NBU inflation targeting regime and the introduction of flexible exchange rates allowed the state to reduce inflation and prevent the accumulation of imbalances in the economy.Conclusions. Based on the results of the study, it can be concluded that the state should help reduce negative external and internal factors by implementing an effective monetary policy, which should regulate foreign exchange activities aimed at accumulating Ukraine's gold and foreign exchange reserves, strengthening the national currency and stabilizing Ukraine's foreign economic relations with other countries. world.